Praise otherwise taffy its use and abuse - Winchip, Bertha (My University, 1891)
Introduction: It was Burdette that said “An ounce of taffy is worth a pound of epitaphy.” There is one thing we can all do but which we all keep stored away as if we were saving it for some great emergency, as if we were afraid in any way to make use of it, and this is our ability to praise. Why is it that we are not willing to give praise where praise is due? Surely we are always ready and willing to find faults and deficiencies, how much better it would be if we were only half so willing to praise what is good and within these. Where one has accomplished some end has been successful in some undertaking, worked hard and faithfully for some house that has been obtained it is nothing more than right that he should be praised for his perseverance in these new energies. It makes me a great deal happier gives him higher ambitions, a determination to do still better the next time, with the thought never to return again to the old standard.
Praise: its use and abuse
Citation: Winchip, Bertha. Praise otherwise taffy its use and abuse. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Praise; Accomplishment; Moral; Theses; Manuscripts (documents)